Screening Children in Post-apocalypse Film and Television - Olson, Debbie (Lexington Books, 2023)
This collection examines the child’s role in contemporary post-apocalyptic films and television.. By exploring the function of child characters within a dystopian framework, this volume illustrates how traditional notions of childhood are tethered to sites of adult conflict and disaster, a connection that often works to reaffirm the “rightness” of past systems of social order.